NLRP3 Inflammasome Activation by MicroRNA-495 Promoter Methylation May Contribute to the Progression of Acute Lung Injury - Youguo Ying; Yong Mao; Min Yao (Elsevier, 2019)
Acute lung injury (ALI) is a pulmonary disorder that causes acute respiratory failure, thus leading to relative high mortality worldwide. However, the molecular mechanisms of ALI remain largely unknown. MicroRNA (miRNA)-dependent control of gene expression at a post-transcriptional level has been recently reported. Herein, we identify a candidate miRNA, miR-495, that affects the progression of ALI. Alveolar macrophages (NR8383) were treated with 1 μg/mL lipopolysaccharide (LPS) to establish a cell-injury model. Combined with the data from western blot, methylation-specific PCR, methylated DNA immunoprecipitation, and chromatin immunoprecipitation assays, NLRP3 inflammasome activation and methylation-dependent repression of miR-495 were found in LPS-exposed NR8383 cells. Dual-luciferase reporter gene assay and miR-495 gain-of-function experiments confirmed that NLRP3 was a target of miR-495. Next, the expression of miR-495 and NLRP3 was overexpressed or silenced to assess their effects on NLRP3 inflammasome activation, alveolar macrophage inflammation, and pyroptosis in vitro. As demonstrated, overexpressed miR-495 alleviated alveolar macrophage inflammation and pyroptosis and inhibited NLRP3 inflammasome activation by negatively regulating the NLRP3 gene. Consistently, elevated miR-495 alleviated lung injury and reduced the neutrophil infiltration and inflammation in rat models of LPS-induced ALI. Taken together, the data in our study demonstrated that methylation of the miR-495 promoter could downregulate miR-495, whose elevation could attenuate the activation of the NLRP3 inflammasome to protect against ALI, which provides novel therapeutic targets for ALI treatment. Keywords: acute lung injury, microRNA-495, NOD-like receptor family pyrin domain containing 3, methylation, inflammasome